4CPS-187 Evaluation of exit prescriptions using computerised provider order-entry system for outpatients. (March 2019) - Abbes, M; Nakab, J; Berdah, S; Bernard, F; Rossi, P; Colombini, N
Abstract : Background: Medication errors are a major source of many risks to patients. The replacement of hand-written orders by the recommended Computerised Provider Order-Entry (CPOE) system 1 makes it possible to issue exit prescriptions more safely. Indeed, outpatients can benefit from pharmaceutical opinions reported during their hospitalisations. Purpose: Outpatients must have a complete record of medication drugs prescribed by the hospital's physicians. To improve patients' clinical care, it is necessary to evaluate the conformity of outpatient medication. Material and methods: We conducted a retrospective study in three hospital departments (digestive surgery, internal medicine, geriatrics) over a 6 month period in order to analyse the conformity and errors in the exit prescription related to CPOE using the software Pharma (Computer Engineering, France) and the Electronic Medical Records (EMR) in Axigate (Pharmagest, France). Results: One-thousand two-hundred and eighty-nine patients were included, of which 933 (72%) had an exit prescription using the software Pharma. Analysis of conformities showed that 204 patients (16%) had no Pharma exit prescription but exit treatments written in the EMR and 152 patients (12%) had no data either in Pharma nor in Axigate. Among the 933 patients, 348 (37%) had a copy/pasted prescription into their EMR and 585 (63%) presented discrepancies or lack of treatment into their EMR. No patient had the exit prescription scanned into their EMR although the software allows it. Two-hundred and seventy patients (29%) had no bodyweight provided even after the pharmacist notifications. Analysis of errors' prescriptions: 255 were incorrect (4% of 7258 total number of drugs prescribed) with 36% drug redundancies, 29% incorrect dosage forms, including 7% of excessive dose and refractory period not respected in 25% cases. These errors were formulated daily by hospital pharmacists as a pharmaceutical opinion in Pharma but not applied by physicians in exit prescriptions. Conclusion: The exit prescriptions are not always recorded with CPOE Pharma. Several nonconformities and errors in outpatients' prescriptions, mainly absence of bodyweight and incorrect drug prescriptions are noted. Hospital pharmacists' initiatives, such as training and communication with physicians, have been set to improve exit prescriptions which will be served by community pharmacies. Reference and/or acknowledgements: Prescription errors related to the use of computerised provider order-entry system for paediatric patients. https://www.sciencedirect.com/science/article/pii/S1386505617300837 No conflict of interest.